Harmonization of Islamic Family Counseling on the Validity of Inherited Land Sale and Purchase Agreements from the perspective of contract law - Dindin Syarief Nurwahyudin; Nakhma'ussolikhah (Ilmu Inovasi Nusantara, 2026)
The sale and purchase of inherited land often give rise to legal disputes due to the intersection of contract law and land law, particularly when not all heirs are involved or when formal land administration procedures are not followed. The core problem addressed in this study is the uncertainty regarding the validity of inherited land sale and purchase agreements that only fulfill contractual requirements but fail to comply with formal land law provisions. This condition often leads to conflicts among heirs and provides limited legal protection for the parties involved. The objective of this study is to analyze the validity of inherited land sale and purchase agreements from the perspectives of contract law and land law, as well as to examine the role of family counseling as an alternative dispute resolution mechanism in resolving inheritance-related land disputes. This study aims to clarify the relationship between substantive contractual validity and the formal legality of land rights transfer. This study employs a normative juridical method using statutory, conceptual, and case approaches. Primary, secondary, and tertiary legal materials are collected and analyzed qualitatively to assess legal norms governing agreements, inheritance, and land registration, as well as their practical implications in dispute resolution. The results indicate that an inherited land sale and purchase agreement is considered valid only when it fulfills both the subjective and objective requirements of contract law, including the consent of all legal heirs, and the formal requirements of land law, namely the execution of a deed by a Land Deed Making Officer (PPAT) and registration at the land office. Family counseling plays a significant role in facilitating mediation, reducing conflict, and encouraging consensus among family members. This study recommends harmonizing contract law and land law regulations, increasing legal awareness among heirs, and integrating family counseling mechanisms to ensure legal certainty, justice, and the protection of parties' rights in inherited land transactions